Development and Validation of the Hungarian Short ECR-R in a Large Nationally Representative Study and a Large Community Study of Mothers Raising Young Children - Dupont, Kinga; Gervai, Judit; Tóth, Ildikó; Török, Szabolcs; Danis, Ildikó (European Journal of Mental Health, 2024)
Introduction: The Hungarian version of the 36-item self-report Experiences in Close Relationships – Revised (ECR-R-HU) questionnaire assessing adult romantic attachment has been published recently. Short versions provide a useful tool for large-scale research and in the clinical field as well.Aims: The present study reports developing and validating the short form of the Hungarian version of the ECR-R (ECR-R-HU-SF).Methods: The development of the short form, data reduction, and item selection were performed in a nationally representative adult (18+) community sample (N = 958; Study 1). The newly developed ECR-R-HU-SF was then tested and validated in a different national study representative of children aged 3–36 months, using data from respondent mothers with diverse sociodemographic backgrounds (N = 980; Study 2).Results: In Study 1, using randomly split subsamples, the ECR-R-HU-SF retained 8 items and confirmed the original two-factor structure of the measure. The subscales showed very good reliability and correlated highly with their corresponding original long versions. Psychometric properties, construct (convergent) validity, sociodemographic associations, and mean population scores for the short-version subscales (Avoidance, Anxiety) were compared with those of the long version. In Study 2, subscales were highly reliable, and scores correlated in the expected directions with related constructs (depressive mood, perceived stress).Conclusions: In summary, the ECR-R-HU-SF is a valid instrument that can be used as an effective screening tool for measuring adult romantic attachment.